A commercial autogenous injection vaccine protects ballan wrasse (Labrus bergylta, ascanius) against aeromonas salmonicida vapA type V - Ramirez-Paredes, J Gustavo; Verner-Jeffreys, David; Papadopoulou, Athina; Monaghan, Sean J; Smith, Louise; Haydon, David; Wallis, Tim S; Davie, Andrew; Adams, Alexandra; Migaud, Herve (Fish & Shellfish Immunology, 2020)
Atypical Aeromonas salmonicida (aAs) and Vibrionaceae related species are bacteria routinely recovered from diseased ballan wrasse used as cleaner fish in Atlantic salmon farming. Autogenous (i.e. farm specific inactivated) multivalent vaccines formulated from these microorganisms are widely used by the industry to protect farmed wrasse despite limited experimental proof that they are primary pathogens. In this study, the components of a commercial multivalent injection vaccine containing four strains of Aeromonas salmonicida and one strain of Vibrio splendidus previously isolated from ballan wrasse in Scotland, were tested for infectivity, pathogenicity and virulence via intra peritoneal injection at pre-deployment size (25-50g) and the efficacy of the vaccine for protection against aAs assessed. Injection with 3.5x109, 8x109 1.8x109 and 5x109 cfu/fish of Vibrio splendidus, V. ichthyoenteri, Aliivibrio logeii and A. salmonicida, respectively, did not cause significant mortalities, lesions or clinical signs after a period of 14 days. IP injection with both aAs and Photobacterium indicum successfully reproduced the clinical signs and internal lesions observed during natural outbreaks of the disease. Differences in virulence (LD50 at day 8-post infection of 3.6x106 cfu/fish and 1.6x107 cfu/fish) were observed for two aAs vapA type V isolates. In addition, the LD50 for Photobacterium indicum was 2.2x107 cfu/fish. The autogenous vaccine was highly protective against the two aAs vapA type V isolates after 700-degree days of immunisation. The RPSFINAL values for the first isolate were 95 and 91% at 1x106 cfu/fish and 1x107 cfu/fish, respectively, and 79% at 1x107 cfu/fish for the second isolate tested. In addition, significantly higher anti aAs seral antibodies (IgM), were detected by ELISA in vaccinated fish in contrast with control (mock vaccinated) fish. These results suggest wrasse can be effectively immunised and protected against aAs infection by injection with oil adjuvanted vaccines prepared with inactivated ...